Notary Authority in Installing Mortgage as Effort to Settle Bad Credit (Second Way Out) - Agung Nugroho; Sukarmi Sukarmi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The role of a notary is very important in helping to create legal certainty and protection for the community, because a notary as a general official has the authority to make authentic deeds, as long as the making of the authentic deed is not specific to other public officials. The implementation of the Deed of Granting Mortgage Rights to Banks is inseparable from the role of the Notary and Land Deed Making Official (PPAT). Activities between the bank and the debtor who transfer the Guarantee Rights guarantee are very interested in making an agreement between them. The approach method used in this study is a sociological juridical approach and is included in descriptive-analytical legal research. The data source used is primary data. The data source used a purposive sample which focuses on selected informants who are rich in cases for in-depth studies. The results of this study are as follows: (1) Installation of Mortgage with APHT which is the authority of the PPAT position in accordance with the provisions of the UUHT is sufficient to be preceded by an underhand Credit Agreement; (2) The notary has a preventive role in credit settlement, ensuring that the rights and obligations of the parties are equally well fulfilled and legally protected and (3) The legal consequence of the installation of the Mortgage is that the Bank can carry out an auction for the execution of the Mortgage through a second way out. If the debtor is stuck. Banks do not need to ask the debtor for approval if they are going to conduct an auction.